RADIOLOGICAL SIGNIFICANCE OF CEMENT USED IN BUILDING CONSTRUCTION IN TURKEY - Turhan, Şeref; Gürbüz, G. (Radiation Protection Dosimetry (2008), Vol. 129, No. 4, pp. 391–396, 2007)
The activity concentration of 226Ra, 232Th and 40K in seven cement types from different factories and grinding plants were measured using a gamma ray spectrometry with HPGe detector. The average activity concentrations observed in the studied cement samples (all from 141 samples) were 40.0+ 27.1, 28.0+ 20.9 and 248.3+ 95.0 Bq kg21 for 226Ra, 232Th and 40K, respectively. The radium equivalent activity (Raeq), the representative level index, the indoor absorbed dose rate and the corresponding annual effective dose were estimated for the potential radiological hazard of the cement. The Raeq values were compared with the corresponding values for cement of different countries. The mean indoor absorbed dose rate (87.4+ 48.5 nGy h21 ) is slightly higher than the population-weighted average of 84 nGy h21 , whereas the corresponding effective dose rate (0.4+ 0.2 mSv y21 ) is lower than the dose criterion of 1 mSv y21 . The obtained results indicate no significant radiological hazards arise from using Turkish cement in building construction.